2022
DOI: 10.1055/s-0041-1740935
|View full text |Cite
|
Sign up to set email alerts
|

Writing a Case Report in Pediatric Surgery: A Comprehensive Guideline

Abstract: An effective case report delivers clear and valuable clinical or surgical information to the medical community. Case reports dealing with pediatric surgical issues raise the medical community's awareness of rare diseases, unusual presentations of common disorders, or novel surgical or nonsurgical treatment approaches. Thus, case reports contribute substantially to medical advance by sharing remarkable or unexpected findings. For this reason, case reports should be prepared with vigilance, and current conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Passive voice tends to make statements long and vague, whereas active voice conveys the message more readily. Most sentences (approximately 70%) of your case report should be in the active voice 23) .…”
Section: Use Of Active Voice 23)25)30)mentioning
confidence: 99%
“…Passive voice tends to make statements long and vague, whereas active voice conveys the message more readily. Most sentences (approximately 70%) of your case report should be in the active voice 23) .…”
Section: Use Of Active Voice 23)25)30)mentioning
confidence: 99%
“…Several full-text reports are available to assist in preparing an interesting and valuable case report. [28][29][30][31][32] The BOX presents a summary of ideas about how to prepare a case report.…”
Section: Case Reports As Educational Toolsmentioning
confidence: 99%
“…As such, it would be worthwhile for academic leaders to introduce other methods of publication such as case reports, narrative reviews, and perspective-type articles that are offered in many medical journals. Although there are publications instructing authors in how to write a case report 1,2 and narrative review, 3,4 we found none cited in PubMed detailing the rationale and steps for writing a perspective article. For authors inexperienced in writing, not considering perspective-type articles is a wasted opportunity for potential publication.…”
mentioning
confidence: 97%